Traumatic Dislocation of the Pisiform Bone - Petrou, Ilias G.; Savioz-Leissing, Claire; Gray, Anne (Journal of Hand and Microsurgery, 2018)
Pisiform dislocation is a rare wrist injury. The limited literature available describes this pathology in the form of case reports. An immediate closed reduction and immobilization is indicated for acute injury while there is a debate in the management of cases with delayed diagnosis or failed closed reduction. In this case, a 32-year-old, right-handed man visited the emergency department with pain at the ulnar side of his left wrist after a fall. The initial management involved immobilization, and the patient was referred to the authors’ specialized clinic 10 days later because of persistence of important ulnar wrist pain. The choice of treatment was pisiform excision without ligament reconstruction with excellent functional results.
Keywords: dislocation; luxation; pisiform; wrist injury